Exploring post‐excavation degradation potential of fungal communities associated with archaeological human remains. (23rd November 2018) - Mircea, C.; Vulpoi, A.; Rusu, I.; Radu, C.; Pârvu, M.; Kelemen, B.
Abstract : Fungal communities associated with three osteoarchaeological samples from distinct archaeological sites (Tărian, Turdaş, Feleacu) in Transylvania, Romania, characterized by similar environmental conditions (wet soils), different historical age and amount of time spent in storage, were examined in order to register site‐ versus storage‐specific species. Physical anthropological taphonomic scoring was correlated with Fourier transform infrared spectroscopy (FTIR) indices in order to characterize mineral and organic bone fraction fluctuations relative to historical age. Molecular‐based species/genera identifications and scanning electron microscopy (SEM) investigations were carried out for the confirmation of dominant taxonomic items.